2016
DOI: 10.3354/esep00166
|View full text |Cite
|
Sign up to set email alerts
|

Tenure and academic deadwood

Abstract: The introduction of market forces into higher education (i.e. marketization) in recent decades goes along with a sharp decline in tenured positions offered, accompanied by polemic voices against tenure. The main claim, that tenure reduces the productivity of senior faculty, has not been thoroughly tested, with existing scarce evidence being controversial. We tested this hypothesis by analyzing the number of publications of 2136 currently full professors of natural sciences, drawn from 123 universities distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Schumann et al suggest that such centers not only enhance the value of faculty contributions but also have the potential to permeate the educational fiber of the entire institution. 23 Development initiatives and academic management policies and procedures that focus on collegiality are especially important, which is to suggest broader mentoring than merely job-specific tasks; but rather, on more career, or even "wholelife" mentoring. 24,25 In doing so, institutions must define what collegiality is within their own context behaviors if they are to shape behaviors through policy, management, and reward systems.…”
Section: Discussionmentioning
confidence: 99%
“…Schumann et al suggest that such centers not only enhance the value of faculty contributions but also have the potential to permeate the educational fiber of the entire institution. 23 Development initiatives and academic management policies and procedures that focus on collegiality are especially important, which is to suggest broader mentoring than merely job-specific tasks; but rather, on more career, or even "wholelife" mentoring. 24,25 In doing so, institutions must define what collegiality is within their own context behaviors if they are to shape behaviors through policy, management, and reward systems.…”
Section: Discussionmentioning
confidence: 99%
“…48 While not necessarily toxic/deleterious, an overabundance of deadweight faculty sets the tone for an unhealthy culture. 49 There have been a number of suggestions proffered for dealing with such faculty; however, many of them revolve around post-tenure review, 13 which is becoming less salient with the increasing number of faculty in non-tenure-track positions. It has been suggested that while challenging, it is indeed possible to develop deadweight faculty, 16 particularly with use of junior colleagues and post-graduate students who might serve to energize and rekindle flames among those who might otherwise be burned out…”
Section: Discussionmentioning
confidence: 99%
“… 11 The antecedents of faculty becoming deadweight have been evaluated, with much of the argument centering around the tenure system, with arguments thatthe processes and expectations required to obtain tenure, as well as the incentives provided by tenure, result inthe development ofstar faculty, 12 yet also create an environment conducive to some faculty becoming deadweights. 13 The awarding of tenure in itself can be viewed as a recognition or reward for those who are or who may become stars, and there is research evincing that tenured faculty are more productive. 14 However, there is also evidence to suggest that a proportion of tenured faculty go into years of “coasting”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the authors point out how important is to distinguish between institutional autonomy and individual academic freedom, and to separate these 2 concepts from the freedom of academics to create and maintain new scholarship fields. Nikolioudakis et al (2015) tested the hypothesis that tenure reduces the productivity of senior faculty, which is the main argument fueling the polemics against tenure. They collected and analyzed the number of publications of 2136 current full professors of natural sciences, from 123 universities distributed across 15 countries, for the period spanning 1996 to 2014.…”
Section: Issues Uncovered In This Theme Sectionmentioning
confidence: 99%